Cerium–zirconium mixed oxide nanostructures for diesel soot oxidation: synthesis and effect of structure. Issue 46 (23rd July 2020) - Teles Aragão Campos, Pablo; Vieira Lima, João Pedro; de Queiroz Silva, Daniele Renata; Oliveira, Claudinei Fabiano; Dias, Sílvia Cláudia Loureiro; Dias, José Alves
Abstract : Nanorods and nanoparticles of Ce0.8 Zr0.2 O2 (CZ) mixed oxides were prepared by different routes and showed good activity for diesel soot oxidation. Abstract : Nanostructured materials have been used in several branches of science and technology. Particulate matter is one of the major air pollution concerns. In this work, nanorods and nanoparticles of Ce0.8 Zr0.2 O2 (CZ) mixed oxides were prepared by different routes, and the use of an organic template was evaluated in diesel soot oxidation. The catalysts were characterized by several techniques including structural analysis (XRD, TEM, N2 adsorption–desorption) and activity (TPR/MS, TPO/MS). A fast TPR/MS method is proposed to calculate hydrogen consumption that can be correlated to the oxygen storage capacity (OSC). It was demonstrated that CZ-nanorods with twice the amount of template in the syntheses (CZ-NRs-2X) were very active for soot oxidation with T 50% at 351 °C, and CO2 and H2 O were the only oxidation products from Printex®-U (Evonik). This catalyst, reported for the first time, was subjected to up to three cycles and it showed fair activity, proving that this morphology is one of the best mixed oxides of CZ for oxidation.